2023
DOI: 10.1128/spectrum.00694-23
|View full text |Cite
|
Sign up to set email alerts
|

The Early Life Microbiota Is Not a Major Factor Underlying the Susceptibility to Postweaning Diarrhea in Piglets

Abstract: This study shows that the fecal microbiota composition and metabolic activity are similar in suckling piglets (13 days after birth) that either later develop post-weaning diarrhea (PWD) or not, which is a major threat for animal welfare that also causes important economic losses and antibiotic treatments in pig production. The aim of this work was to study a large cohort of piglets raised in separates environments, which is a major factor influencing the early life microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Moreover, in the same study by Rattigan et al, maternal probiotic supplementation increased the abundance of Lactobacillus in the offspring faeces on day 118 postweaning [20], supporting the theory that the pioneer microbiota influences the microbial communities later in the pigs life. In contrast, Beaumont et al concluded that the early life microbiota is not a major factor underlying the susceptibility to diarrhoea in the postweaned pig [205]. These studies suggest that modulation of the offspring's microbiota preweaning may be an effective therapeutic strategy to reduce the proliferation of pathogens and prevalence of diarrhoea in the offspring postweaning.…”
Section: Early Life Gut Colonization-plasticity Of the Pioneer Microb...mentioning
confidence: 91%
“…Moreover, in the same study by Rattigan et al, maternal probiotic supplementation increased the abundance of Lactobacillus in the offspring faeces on day 118 postweaning [20], supporting the theory that the pioneer microbiota influences the microbial communities later in the pigs life. In contrast, Beaumont et al concluded that the early life microbiota is not a major factor underlying the susceptibility to diarrhoea in the postweaned pig [205]. These studies suggest that modulation of the offspring's microbiota preweaning may be an effective therapeutic strategy to reduce the proliferation of pathogens and prevalence of diarrhoea in the offspring postweaning.…”
Section: Early Life Gut Colonization-plasticity Of the Pioneer Microb...mentioning
confidence: 91%